A Prospective Study of Offending Patterns of Youth Homicide Offenders Into Adulthood: an Examination of Offending Trajectories and the Crime Mix Posthomicide - McCuish, Evan C. (Youth violence and juvenile justice, 2018)
Although youth homicide offenders (YHOs) are portrayed as a group that warrants considerable attention from the justice system because of their high likelihood of future offending, little is known about this group’s offending trajectories and the nature of posthomicide offenses in adulthood. These questions were investigated using a sample of male and female YHOs (n = 26), violent YHOs (n = 358), and nonviolent YHOs (n =139), all of whom were followed prospectively into adulthood. First, the prevalence of adult recidivism did not vary across the three groups. Second, YHOs were more frequent offenders prior to their homicide offense than after their homicide offense, and when they did offend posthomicide, it was typically a nonserious crime. Third, YHOs did not differ from other offenders in their association to a specific offending trajectory. These findings are discussed in the context of assessment and treatment of serious and violent youth.